2018
DOI: 10.3390/ijms19061653
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Running Ameliorates Destruction of Articular Cartilage and Subchondral Bone, Not Only Synovitis, in a Rheumatoid Arthritis Rat Model

Abstract: We analyzed the influence of treadmill running on rheumatoid arthritis (RA) joints using a collagen-induced arthritis (CIA) rat model. Eight-week-old male Dark Agouti rats were randomly divided into four groups: The control group, treadmill group (30 min/day for 4 weeks from 10-weeks-old), CIA group (induced CIA at 8-weeks-old), and CIA + treadmill group. Destruction of the ankle joint was evaluated by histological analyses. Morphological changes of subchondral bone were analyzed by μ-CT. CIA treatment-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…In experimental models of arthritis, it has been confirmed that mechanical stress increase joint inflammation, stimulate the progression and chronicity of arthritis and structural damage [16,17,48]; besides, the mechanical stress decrease the bone quality [16]. In contrast to our findings, other studies in the AIA model have shown an anti-inflammatory effect of PE in some parameters such as synovial hyperplasia [49,50], and joint destruction [51].…”
Section: Discussionsupporting
confidence: 54%
“…In experimental models of arthritis, it has been confirmed that mechanical stress increase joint inflammation, stimulate the progression and chronicity of arthritis and structural damage [16,17,48]; besides, the mechanical stress decrease the bone quality [16]. In contrast to our findings, other studies in the AIA model have shown an anti-inflammatory effect of PE in some parameters such as synovial hyperplasia [49,50], and joint destruction [51].…”
Section: Discussionsupporting
confidence: 54%
“…Following past reports, we conducted immunostaining for TNF-α and Cx43 [17]. TNF-α expression was aggravated throughout the synovial membranes, but the level of staining was significantly lower for the T group than for the control group (Figure 3A,C).…”
Section: Resultsmentioning
confidence: 76%
“…We also analyzed the role of Cx43 as a key gene in synovial membrane inflammation in RA. Studies have shown that, in collagen-induced arthritis (CIA) rats, Cx43 induces joint destruction through pro-inflammatory cytokines such as TNF-α and IL-6, and that joint destruction is suppressed not only if Cx43 expression is suppressed in small interfering ribonucleic acid, but also by suppressing Cx43 expression through treadmill running as well [17,23,24]. Cx43 expression changes with mechanical stress such as stretching stimuli and shearing forces in cardiomyocytes and osteocytes [25,26]; therefore, it may also change due to the addition of mechanical stress to the synovial membranes by treadmill running.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the world's refractory diseases. 1,2) Leflunomide (LEF), a new type of immunomodulator, has been commonly used alone or in combination with methotrexate for the treatment of RA as a kind of disease-modifying anti-rheumatic drugs (DMARDs). 3) LEF is a derivative of isoxazole, which is converted to teriflunomide (TEF, A771726) through the gastrointestinal tract and liver.…”
Section: Introductionmentioning
confidence: 99%